THE EFFECT OF CURRENT RATIO ON RETURN ON ASSETS AT PT. ASTRA AGRO LESTARI, TBK PERIOD 2008-2018 - Irada Sinta; Nadya Jasmine; Lika Andira BR Pinem; Nailul Ulfah; Ulfia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This study aims to determine the effect of the Current Ratio on Return on Assets at PT. Astra Agro Lestari, Tbk Period 2008-2018. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Current Ratio obtained an average value of 127.09%. The return on variable assets obtained an average value of 25.88%. Current Ratio has a positive and significant effect on Return On Assets with a regression equation value of Y = 9.112 + 0.132X, and a correlation coefficient value of 0.660 or has a strong level of relationship with a determination value of 43.5%. Hypothesis testing obtained a significance of 0.027 > 0.05.